The involvement of working memory during retrieval from episodic memory. - Kocsis, Marton F.; Farrell, Simon (Memory & Cognition, 2026)
While the role of attention via WM during free recall has been well established in the dual-task literature, the potential role of storage-based aspects of WM in episodic retrieval has yet to be explored, particularly outside the context of individual differences. We enforced a storage-based WM load during the recall window of a free recall-based task to examine effects on a variety of episodic recall characteristics. We assessed the effects of the load on benchmark effects from the free-recall literature (primacy, recency, lag-recency) and the rate of memory search. While load affected overall recall accuracy, there was otherwise no reliable effect of a storage-based WM load on the benchmark effects of free recall. The impairment of recall accuracy under WM load without any commensurate effect on fundamental aspects of episodic retrieval is challenging for perspectives in which the differences in episodic retrieval uniquely arise from effects on the rate of memory search, as has usually been observed in both the dual-task and WM literatures.